Nomadic education for national integration in Nigeria - Wonah, E. Dominic; Bullem, G. Anthony (e-Pedagogium, 2020)
The need for the education of the nomads cannot be over-emphasized. Nigeria's population is characterized with many occupations and methods of farming. A feature of the nomads is movement from place to place in a quest for pasture, fertile soil, fishing ponds or rivers and hunting grounds. Importantly, they roam about, and that is why they are called nomads. This group of farmers needs education. Since education has been described as an "instrument for national development and change" by Federal Policy on Education NPE (2010), it is necessary for the migrating farmers to be given an education. This article is therefore investigating how the migrating farmers will benefit from the education intended for them. It is therefore a position paper as information garnered for this paper is extracting from articles, newspapers and journals. The aim of this paper is therefore to examine the strategies adopted in view of repositioning lapses encountered earlier between nomads and staple farmers who are in perpetual disagreement.
Keywords: nomads; education; crop farmers; conflict resolution.